The Role of Religion Course lecturers in moral health promotion of students - Mahdi Fani; Morteza Abdoljabari; Mostafa Esmaeili; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: This paper examines the role of professor of Islamic courses in the promotion of moral health of students. Therefore, it is essential to clarify the position of professors teach Islamic courses in Religious thoughts. In this context, with reference to religious texts we can perceive every person who plays the master teacher role is responsible for education as the Prophet(PBUH) at a lesser extent. This task will only become meaningful when a relationship exists between science and ethics or education and training. Hence, we have studied the comments of Muslim and non-Muslim scientists  to link science and ethics and have evaluated the importance of attention to ethics in universities around the world. And in the end we concluded Iranian universities, In addition to the rules of conduct, have paid special attention to the moral content of academic courses and also human factor for transferring of these concepts to students, and ultimately achieve a higher level of moral health Keywords: Islamic Education Teachers, Students, Moral Health For downloading the full-text of this article please click here.